On Concomitants of Dual Generalized Order Statistics for a Bivariate Inverse Exponential Distribution (European Journal of Pure and Applied Mathematics, 2018)
The concomitants of Dual Generalized Order Statistics for InverseExponential distribution has been studied. Specifically the distributionalproperties of r--th concomitant and joint distribution of r--th and s--thconcomitant of dual generalized order statistics have been studied whensample is available from a bivariate inverse exponential distribution.